Pengkajian Kitab Kuning Sebagai Tonggak Keilmuan di Pondok Al Utsmani - Mochammad Achsan Auza’i; Uswatun Khasanah; Muhammad Luki Faturrokhman (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2023)
Pesantren in Indonesia have experienced changes in orientation but still try to maintain their uniqueness and distinctiveness. One of the preserved legacies is the custom of sanad in religious learning. Pesantren have a long history and function as centers for the dissemination of traditional Islamic knowledge as well as the training of ulama. However, pesantren also face challenges in dealing with modernization. Therefore, it is important to integrate general science and technology in the pesantren curriculum. This research uses a descriptive qualitative approach by analyzing written data and direct interviews with relevant informants. This research emphasizes the importance of maintaining the sanad in the study of yellowclassical books. Sanad must be related to the author of the book to strengthen continuity in science. This is an important tradition that is still upheld in pesantren.